Validity of Physics E-Modules Based on an Inquiry Model Integrated with the Science, Environment, Technology, and Society Approach to 21st Century Skills - Westi Widia Wati; Syafriani Syafriani* (JIPI (Jurnal IPA dan Pembelajaran IPA), 2023)
Education for the 21st century combines knowledge, abilities, and attitudes with a command of information and communication technologies. The role of education is very important as part of an effort to build national character and produce millennials who are innovative, creative, and ready to face global challenges. 21st-century skills are one of the skills that students must have to face global challenges. 21st century skills include critical thinking, creativity, collaboration, and communication, otherwise known as "4C skills." 21st-century skills are also very much needed in learning physics. One of the best teaching materials for enhancing students' 21st-century skills is an e-module built on the inquiry model and the science, environment, technology, and society (SETS) approach. The goal of this study was to establish the validity, practicability, and efficacy of e-modules created using the SETS approach integrated inquiry model in increasing students' 21st century competencies. This type of research is called development research (RD). This development procedure refers to the Plomp development model, which has three stages: preliminary research, prototyping, and assessment. E-module validation is reviewed from four aspects: the substance of the material, the learning design, the appearance, and the use of the software. The average score obtained for the substance component of the material, the learning design, the appearance, and the use of the software is in a very valid category. Based on these data, it can be concluded that the inquiry model-based e-module integrated with the SETS approach is in the "very valid" category